The Influence of Personalized AI on Consumers’ Engagement in E-commerce among Generation Z in Penang - Yeo, Zi Xwan; R. Chandrashekar (Research in Management of Technology and Business, 2026)
The rise of artificial intelligence (AI) has reshaped the mechanisms of consumer interaction and strategic decision-making in e-commerce. This shift is particularly relevant among Generation Z in Penang, Malaysia who are active digital users and potential online shoppers. This study is to identify the influence of personalized AI on consumers’ engagement in e-commerce among generation Z in Penang. The research investigated the influence of AI networking recommendation, AI personalized feed, and AI quality on consumers’ engagement in e-commerce platforms. This research adopted a quantitative research design, collecting data from 384 Generation Z respondents in Penang using convenience sampling. The collected data analyzed by Statistical Package for Social Sciences (SPSS), conducted empirical analysis using 317 valid questionnaires included descriptive analysis, normality test and correlation analysis. Researcher found that the AI quality can significantly influences Gen Z consumers’ engagement in e-commerce. These results can guide digital marketers and e-commerce platforms to optimize AI personalization strategies and build consumer trust effectively.